The global you - Bloch, Susan (Marshall Cavendish International (Asia), 2011)
Millions of people are now global business workers of some kind. Even though they might not use the term as such, they are buying, selling, managing and operating all over the world, but often have little preparation for the job. This book provides ten practical ways to enable the Global You to think, behave and operate in the appropriate global way.